(untitled) (Research, Society and Development, 2021)
Objective: to compare the manifestation of vocal fatigue in university professors of active and traditional methodology in the period of remote classes due to the covid-19 pandemic. Methods: The study included 106 university professors from a federal educational institution, who were grouped according to the methodology used. The traditional methodology group (MT) was composed of 59 teachers (31 men, 28 women), with a mean age of 44.07 ± 9.12. The active methodology group (AM) was composed of 47 teachers (20 men, 27 women), with a mean age of 42.89 ± 9.08. The following protocols were used: Vocal Fatigue Index (IFV), Voice Disorder Screening Index (ITDV) and structured anamnesis The analysis involved comparison between groups and comparison between genders in each group. Results: The IFV showed no statistical difference in any of its factors, however, with the exception of the vocal restriction factor, all other test parameters were above the cutoff values. ITDV and the workload of remote classes also did not present a statistically significant difference between the groups. Women had higher IFV values ​​than men, especially for active teaching methodology. Conclusion: University professors presented manifestations of vocal fatigue, vocal limitation physical discomfort associated with voice use and difficulty in recovery after vocal rest, regardless of the teaching methodology used.